PENGARUH BAURAN PEMASARAN TERHADAP MINAT BELI KONSUMEN PADA TOKO DONAT MADU LAPAI - Jhon Fernos; Ahmad Syarief Ayadi (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2023)
The purpose of this study was to examine the effect of product, price, location, and promotion variables on consumer buying interest at the Lapai Honey Donut Shop. Collecting data by distributing questionnires to 99 respondents using total sampling technique, where the entire population is sampled, using multiple linear regression testing with the help of the SPSS application. The result of this study indicate that the product has a positive effect on consumer buying interest, while price, location and promotion have no effect on consumer buying interest